Field Performance and Economic Analysis of Rehabilitated Pavement Sections with Engineered Stress Relief Course Interlayers. Issue 5 (May 2019) - Habbouche, Jhony; Hajj, Elie Y.; Piratheepan, Murugaiyah; Sebaaly, Peter E.; Morian, Nathan E.
Previous studies showed that the use of a stress relief course asphalt concrete (AC) interlayer (fine-graded asphalt mixture) between an AC overlay and the milled AC surface is a promising technique to mitigate reflective cracking. A performance-based mix design specification for an engineered stress relief course (ESRC) AC interlayer was developed and implemented in Nevada on two field projects. The projects were completed in summer of 2015 and 2016 on a U.S. route (US95, Las Vegas) and a residential road (Hidden Valley, Reno) in Nevada, respectively. The performance evaluation of field-produced mixtures collected during construction showed good stability, and increased resistance to fatigue and reflective cracking that can be attributed to the increased asphalt binder content and the finer aggregate gradation, thus making ESRC a promising technique to mitigate reflective cracking. This was also supported by the distress survey data collected throughout the up-to-date service life of the projects. The pavements with ESRC interlayer showed excellent performance thus far (after 2 to 3 years) when compared with the control sections, as demonstrated with a much lower level of cracking reflected in the AC overlay. A simple life cycle cost analysis was performed based on the observed field distresses from each project. The cost analysis showed that even though the ESRC mixture has a higher initial cost of materials, the agency and user life cycle costs per lane mile are lower and resulted in an average cost saving of 23%. In summary, based on the findings from this study, interlayer AC mixes designed using the presented ESRC performance-based mix design method should be used in Nevada.